Radiocarbon ages of sediment core MD05-2896 - Liang Dong; Li Li; Qianyu Li; Hui Wang; Chuanlun L Zhang (PANGAEA, 2024)
To derive an age-depth models for the core radiocarbon ages were measured on the planktonic foraminifera species Globigerinoides ruber albus.